A docência na educação infantil: a visão de professoras de um CEI da cidade de São Paulo - Fagundes, Valquiria Regina (2014)
This study searches to analyse the comprehension the child education teacher (from the 0 to 3 year-old segment) have regarding their initial and continued formation, and their teaching activity. The theoric reference is based on authors who defend a critical-reflexive concept of education and a childhood and children education concept which lays on the social-historical perspective. The research Universe gathers facts of a CEI (Child Education Center) from São Paulo public educational system, located in the south zone of the city; participants were the pedagogical coordinator and 14 teachers. In order to raise facts, procedures such as document analysis, filling out of a semistructured guided questionnaire and registering of daily basis school procedure notes, elaborated by the researcher who also taught at the CEI, were carried out. It is to be highlighted that the focus of the information registering carried out by the researcher in collective situations such as the JEIF (Integral Special Formation Journey) encounters were the speeches, dialogues, gestures and behavior of the teachers about what they think and practice regarding the following topics: child education practice routine, autonomy of the children and compromising with child education teaching. The analysis on teaching formation was made based on the thinking of the impacts of the 1960s educational system military reformation and its lingering implications on the current Brazilian educational system. The results reveal that, according to the teachers' evaluation, the proposal on formation of graduation courses did not favor the theory-practice relation; and that the teachers conceive their practice in a manner that is associated with the devalorization of the teaching in child education by community and society in general, especially when the activity is attached to the assistencialist vision linked with the mere care about hygiene and feeding the children.